2012
DOI: 10.1371/journal.pone.0045061
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Metabolic Alterations Exist in Mutant PI3K Cancers, but Only Glucose Is Essential as a Nutrient Source

Abstract: Targeting tumour metabolism is becoming a major new area of pharmaceutical endeavour. Consequently, a systematic search to define whether there are specific energy source dependencies in tumours, and how these might be dictated by upstream driving genetic mutations, is required. The PI3K-AKT-mTOR signalling pathway has a seminal role in regulating diverse cellular processes including cell proliferation and survival, but has also been associated with metabolic dysregulation. In this study, we sought to define h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…In a study of breast cancer and normal breast tissues, myo ‐inositol and glucose were lower in the tumor samples 45. The PI3K‐AKT‐mTOR pathway is perturbed in many cancers and it was recently reported that cell lines with mutated PI3K possess a highly glycolytic phenotype and withdrawal of glucose cannot be compensated by addition of alternative nutrients 44. Whether or not our observation of an ∼2‐fold attenuation of myo ‐inositol tumor concentrations (Fig.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In a study of breast cancer and normal breast tissues, myo ‐inositol and glucose were lower in the tumor samples 45. The PI3K‐AKT‐mTOR pathway is perturbed in many cancers and it was recently reported that cell lines with mutated PI3K possess a highly glycolytic phenotype and withdrawal of glucose cannot be compensated by addition of alternative nutrients 44. Whether or not our observation of an ∼2‐fold attenuation of myo ‐inositol tumor concentrations (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Myo ‐inositol is a metabolic precursor of the inositol phosphate second messengers, phosphatidylinositol membrane lipids, and the phosphoinositide lipid signaling molecules 34. The PI3K‐AKT‐mTOR pathway, which has been associated with induction of aerobic glycolysis and tumor metabolic remodeling,43, 44 requires inositol triphosphate (PI3), and thus myo ‐inositol as a substrate. Myo ‐inositol is synthesized from glucose34 and thus diminution of cellular glucose by enhanced metabolism is likely to impact cellular myo ‐inositol.…”
Section: Discussionmentioning
confidence: 99%
“…An emphasis on the PI3K pathway was made because of the role of mTOR and other pathway components in glucose homeostasis (Elstrom et al, 2004;Sun et al, 2011). It has also been reported that PIK3CA mutant tumours have a high rate of glucose uptake and dependence on glycolysis (Cantley, 2012;Foster et al, 2012). GC cells were used because of the commonly hypoglycaemic state of gastric tumours (Hirayama et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, the energy source driving cancer cell proliferation results from aerobic glycolysis [39]. It is now becoming increasingly clear that cancer arises as a consequence of dysregulated metabolism in response to an altered energy status and endocrine factors [40].…”
Section: Discussionmentioning
confidence: 99%